Effect of Percent Fines in Pelleted Diets on Growth Performance of Grow-Finish Pigs During Three Phases of Production - Patrick A. Badger; Haley K. Otott; Adam Donnelly; Charles R. Stark; Chad B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2022)
Swine feed is commonly pelleted to improve F/G, feed handling characteristics, and bulk density. However, the degree of improvement in F/G of pigs depends on pellet quality or the percent fines at the feeder. The objective of this study was to determine if the response to pellet quality was dependent on the BW range of grow-finish pigs. Therefore, a total of 350 pigs (initially 80 lb; line 600 × 241, DNA) were randomly placed in 35 pens with 10 pigs per pen (5 barrows and 5 gilts per pen). All pigs were fed a common diet until the onset of the first experiment. At this time, pens of pigs were weighed to determine average pig weight per pen and split into 7 blocks based on average pen weight. Treatments were randomly assigned to pens within block. There was a total of 5 treatments with 7 replications per treatment. For Exp. 1, 2, and 3, pigs were fed treatments for 20 days from 96 to 150 lb, 21 days from 179 to 234 lb, and 20 days from 260 to 317 lb, respectively. Between each experiment, a 10-day washout period was utilized to mitigate any residual effects from the previous experiment and pens were rerandomized to treatment before the start of each experiment. Treatments consisted of 10% fines (screened pellets), pellets with increasing fines inclusions (45, 65, and 85% fines), and mashed feed. Experiment 1 (96 to 150 lb) treatments contained 90.4, 67.6, 46.4, and 12.5% fines at the feeder. There was no evidence of differences in ADG or ADFI in pigs fed the mash diet compared to those fed any of the pelleted treatments. However, pigs fed pellets with 12.5% fines had improved (P<0.05) F/G compared to those fed mash diets. Pig ADFI and total feed cost increased (linear,P>0.006) in those fed pelleted diets with an increasing percentage of fines. Pigs fed pelleted diets with increasing percentage of fines (linear,P= 0.002) had poorer F/G. Experiment 2 (179 to 235 lb) treatments consisted of 86.0, 60.5, 43.6, and 15.5% fines at the feeder. There was no evidence of differences in ADG. Pigs fed 86.0% fines had a tendency for increased (P<0.1) ADFI and poorer F/G when compared to the mash diet. Therefore, total feed cost increased (P<0.05) for pigs fed pellets with 86.0% fines when compared to pigs fed the mash diet. However, pigs fed pellets with 15.5% fines had improved (P<0.05) F/G compared to those fed mash diets. For pigs fed pelleted diets, increasing percentage of fines increased (linear,P= 0.016) ADFI which resulted in poorer (linear, P<0.02) F/G, total feed cost, and income over feed cost (IOFC). Experiment 3 (260 to 317 lb) pelleted diets contained 83.6, 65.1, 41.8, and 9.6% fines at the feeder. There was no evidence of differences in ADG or ADFI for pigs fed pellets with 65.1, 41.8, or 9.6% fines compared to those fed the mash diet. Pigs fed 83.6% fines had increased (P<0.05) total feed cost per pig and a tendency for increased (P<0.1) ADFI when compared to pigs fed the mash diet. Pig F/G improved(P<0.05) when fed 9.6 and 41.8% fines compared to those fed mash diets. Pigs fed 65.1% fines had a tendency for improved (P<0.1) F/G when compared to pigs fed the mash diet. Income over feed cost improved (P<0.05) in pigs fed pellets with 9.6% fines when compared to those fed the mash diet. Pig F/G became poorer (linear,P= 0.0056) as percent fines increased in the pelleted diets. Pelleted diets with fines increasing from 9.6 to 83.6% tended to increase (linear,P= 0.0874) total feed cost. In conclusion, feeding pigs 12.5, 15.5, and 9.6% fines in Exp. 1, 2, and 3 improved F/G by 4.1, 4.5, and 6.7%, respectively, compared to pigs fed mashed diets. Increasing the percent fines from 12.5 to 90.4%, 15.5 to 86.0%, and 9.6 to 83.6% reduced F/G of pigs by 5.9, 8.6, and 6.4% for Exp. 1, 2, and 3, respectively.
Keywords: pellet fines; pelleting; grow-finish pigs